Integrating carbon emissions from lakes and streams in a subarctic catchment. Issue 3 (3rd September 2013) - Lundin, Erik J.; Giesler, Reiner; Persson, Andreas; Thompson, Megan S.; Karlsson, Jan
Abstract: [1] Northern inland waters emit CO2 and CH4 to the atmosphere but the importance of these emissions is poorly understood due to a lack of integrated catchment‐scale estimates of carbon (C) emissions from lakes and streams. In this study we quantified the annual emission of CO2 and CH4 from 27 lakes and 23 stream segments in a 15 km 2 subarctic catchment in northern Sweden. All lakes and streams were net sources of C to the atmosphere on an annual basis. Streams dominated (96%) the aquatic CO2 emission while lakes (61%) dominated the aquatic CH4 emission. Total aquatic C emission from the catchment was estimated to be 9.1 g C m −2 yr −1 (98% as CO2 ). Although streams only accounted for 4% of the aquatic area in the catchment, they accounted for 95% of the total emission. The C emissions from lakes and streams were considerably larger than previously reported downstream waterborne export of C from the catchment, indicating that the atmospheric losses of C in the aquatic systems are an important component in the catchment C balance. Key Points: Streams and lakes are atmospheric sources of CO2 and CH4 Streams dominate the CO2 emissions while lakes dominate the CH4 emissions Carbon emission was considerably larger than the downstream carbon export